Regional Development Banks: Performance and Regulations - Endah Suci Damayanti; Nera Marinda Machdar; Adler Haymans Manurung (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this article is to provide an explanation of regional development banks and is accompanied by various descriptions of research results from various literature articles from various sources. The method used in this article provides a graphical qualitative model derived from literature review articles originating from various sources from journals, related existing regulations and other sources from the internet. Regional Development Banks (BPD) are an important part of the bank business group in Indonesia. BPD has a strategic role in supporting economic development in the region. OJK Regulation No. 12/POJK.03/2020 concerning Business Activities and Obligations of Regional Development Banks has been established to regulate BPD operations and ensure that the performance and soundness of banks are maintained.